2013
DOI: 10.1074/jbc.m113.468215
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Architecture of the Golgi Dsc E3 Ligase Required for Sterol Regulatory Element-binding Protein (SREBP) Cleavage in Fission Yeast

Abstract: Background: Fungal sterol regulatory element-binding protein cleavage requires the Golgi Dsc E3 ligase complex of undefined structure. Results: Biochemical and bioinformatic analyses provide insight into Dsc E3 ligase architecture, indicating that Dsc2 is a ubiquitin-binding rhomboid pseudoprotease. Conclusion:The five Dsc E3 ligase subunits form subcomplexes and display defined connectivity. Significance: Multisubunit E3 ligase complexes in the ER and Golgi exhibit conserved subunit organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 43 publications
(86 reference statements)
1
38
0
Order By: Relevance
“…In the absence of Dsc2, Dsc3, or Dsc4, Dsc1 migrated with an intermediate mobility as compared with the mature and deglycosylated forms (Fig. 3A, lane 2) (8). Unexpectedly, we observed that Dsc1 mutants lacking E3 ligase activity also displayed incomplete glycosylation (Fig.…”
Section: Mature (M) Intermediate (I) Deglycosylated (D)mentioning
confidence: 68%
See 4 more Smart Citations
“…In the absence of Dsc2, Dsc3, or Dsc4, Dsc1 migrated with an intermediate mobility as compared with the mature and deglycosylated forms (Fig. 3A, lane 2) (8). Unexpectedly, we observed that Dsc1 mutants lacking E3 ligase activity also displayed incomplete glycosylation (Fig.…”
Section: Mature (M) Intermediate (I) Deglycosylated (D)mentioning
confidence: 68%
“…Interestingly, complete glycosylation of Dsc1 requires Dsc2, Dsc3, and Dsc4 (8). In the absence of Dsc2, Dsc3, or Dsc4, Dsc1 migrated with an intermediate mobility as compared with the mature and deglycosylated forms (Fig.…”
Section: Mature (M) Intermediate (I) Deglycosylated (D)mentioning
confidence: 89%
See 3 more Smart Citations